Sensitive Determination of Selected Drug Active Compounds in Wastewater Matrices by LC-QTOF-MS/MS after Vortex Assisted Binary Solvents Dispersive Liquid-Liquid Microextraction - Kocoglu, E. Seda; Sozudogru, Onur; Komesli, Okan T.; Yilmaz, Alper E.; Er, Elif Ozturk; Bakirdere, Sezgin (OXFORD UNIV PRESS, 2020)
Binary solvent dispersive liquid-liquid microextraction (BSDLLME) was combined with liquid chromatography quadrupole time-of-flight tandem mass spectrometry (LC-QTOF-MS/MS) for the simultaneous determination of selected drug active compounds with high accuracy and precision. Optimization studies for the extraction parameters were carried out to lower the detection limits of seven drug active compounds. Under the optimum experimental conditions, the limits of detection (LOD) and quantitation (LOQ) values were calculated in the range of 0.01-6.1 and 0.05-20 ng mL(-1), respectively. Recovery studies were also carried out with wastewater matrix to check the applicability of the developed method. The percent recovery values ranged between 95-105 and 90-116% for 75 and 125 ng mL(-1) spiked samples, respectively. The recovery results obtained established the applicability of the developed method for the quantification of all analytes in the selected matrix. Thus, the developed method can be used for the simultaneous determination of analytes with high accuracy and precision.
Keywords: Binary solvents dispersive liquid-liquid microextraction (BS-DLLME); Drug active compounds; LC-QTOF-MS/MS; SOLID-PHASE EXTRACTION; PHARMACEUTICAL RESIDUES; MASS-SPECTROMETRY; TREATMENT PLANTS; SAMPLES; QUANTIFICATION; ANTIBIOTICS; METABOLITES; HONEY; MS; Chemistry